Replicated photonic crystals by atomic layer deposition within holographically defined polymer templates - Graugnard, E; Roche, O; Dunham, SN; King, J; Sharp, D; Denning, R; Turberfield, A; Summers, C (2009)
We report the replication of holographically defined photonic crystals using multistage atomic layer deposition. Low- and high-temperature atomic layer depositions were combined with selective etching to deposit and remove multiple conformal thin films within three-dimensional polymer templates. Using intermediate Al 2 O 3 inverse replicas, temperature- sensitive SU-8 photonic crystal templates were faithfully replicated with TiO 2 and GaP, greatly increasing the dielectric contrasts of the photonic crystals. Optical measurements are in good agreement with the calculated band structures. © 2009 American Institute of Physics.